ANALISIS PERBEDAAN PERSEPSI MAHASISWA AKUNTANSI UNIVERSITAS JAMBI MENGENAI FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KARIR - Wirmie Eka Putra (InFestasi, 2011)
This research aim to know difference of perception among accountancy student to chosening career as public accountant, company accountant, educator accountant, and governmental accountant about financial reward, professional training, professional confession, social values, work environment, consideration of market employ and personality. And kind of career most accounting students interested and uninterested. The sample of this research was taken about 135 respondents from the population 203 respondents. The data collection method is using survey with questionnaires instrument. The normality of the data was tested by implementing Kolmogorof Smirnov, the validity of the data was tested by implementing Correlated Item-Total Correlation and the reliability of the data was tested by implementing the Cronbach Alpha. This research is comparative research so hypothesis test in the research is using Kruskall-Wallis test. The result shows that the difference accounting student perception about factors influencing the career choices of the accounting student are financial reward, professional training, professional confession, work environment and consideration of market employ. But they don’t think more about social values and personality.